2018
DOI: 10.1016/j.comcom.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Energy sustainable paradigms and methods for future mobile networks: A survey

Abstract: Abstract-In this survey, we discuss the role of energy in the design of future mobile networks and, in particular, we advocate and elaborate on the use of energy harvesting (EH) hardware as a means to decrease the environmental footprint of 5G technology. To take full advantage of the harvested (renewable) energy, while still meeting the quality of service required by dense 5G deployments, suitable management techniques are here reviewed, highlighting the open issues that are still to be solved to provide eco-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 110 publications
0
22
0
Order By: Relevance
“…We can normalize the effective irradiance, I eff with respect to the maximum radiation of 1 kW/m 2 , obtaining the radiation rate F (t, N ) = 0.001·I eff (t, N ). Then, we can compute the light-generated current for a single solar cells as i l (t, N ) = i sc F (t, N ) and obtain i out (t, N ) for a single solar cells using equation (5). Finally, the total current generated by the solar module is i M out (t, N ) = n p i out (t, N ).…”
Section: B Solar Panel Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We can normalize the effective irradiance, I eff with respect to the maximum radiation of 1 kW/m 2 , obtaining the radiation rate F (t, N ) = 0.001·I eff (t, N ). Then, we can compute the light-generated current for a single solar cells as i l (t, N ) = i sc F (t, N ) and obtain i out (t, N ) for a single solar cells using equation (5). Finally, the total current generated by the solar module is i M out (t, N ) = n p i out (t, N ).…”
Section: B Solar Panel Modelmentioning
confidence: 99%
“…Several works in the literature [3], [4], [5] discuss the integration of solar energy sources into communication networks as a way to reduce their energy consumption and conclude that such an integration is feasible only with the introduction of an intelligent control system able to manage the intermittent and erratic energy budget from renewable sources.…”
Section: Introductionmentioning
confidence: 99%
“…With these predictions, both public and private initiatives started to develop the fifth generation (5G) of cellular systems more than a decade ago. The design goals for such networks to clearly improve upon the existing technologies were quite ambitious [2,3], aiming, among others, at 1-10Gbps connections, 1 ms latency, 1000x bandwidth, 10-100x connections and, the one that targets this work, 90% of energy consumption to reduce the increasing carbon footprint of this newly 5G networks [18].…”
Section: Introductionmentioning
confidence: 99%
“…The survey paper [23], presents a taxonomy of existing energy sustainable paradigms and methods to address energy savings in network elements (i.e., BSs) equipped with EH capabilities. Here, the authors discuss the shortcomings of previous studies related to efficient energy management procedures, the lack of relevant discussion related to the integration of EH into future networks, and lastly, energy self-sustainability in future networks.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the authors discuss the shortcomings of previous studies related to efficient energy management procedures, the lack of relevant discussion related to the integration of EH into future networks, and lastly, energy self-sustainability in future networks. The current work is a technical contribution where we address some of the shortcomings that were identified in [23], also proposing the use of Machine Learning (ML) tools for pattern forecasting and adaptive control schemes for decision making. In addition, this work is in line with the research topics which can be found in our review paper [24].…”
Section: Introductionmentioning
confidence: 99%